Comparison of clinical outcomes between conventional in vitro fertilization and intracytoplasmic sperm injection in poor responders with only single oocyte retrieved - Chao-Yun Wu; Tian-Jeau Huang; Yuh-Ming Hwu; Robert Kuo-Kuang Lee; Ming-Huei Lin (Elsevier, 2023)
Objective: To compare the clinical outcomes between conventional insemination (IVF) and intracytoplasmic sperm injection (ICSI) in poor responders with only a single oocyte retrieved. Materials and methods: This is a retrospective case-control study. Couples who were treated with assisted reproductive technology (ART) with a single oocyte retrieved in Mackay Memorial Hospital from 1996 to 2016 were recruited. All data were categorized into three groups, according to their fertilization method and semen quality: group A, conventional insemination with non-male factor (IVF-NMF, n = 115), group B, ICSI with male factor (ICSI-MF, n = 30), and group C, ICSI with non-male factor (ICSI-NMF, n = 49). Results: No statistically significant difference was observed between IVF and ICSI groups in pregnancy outcomes, including the chemical or clinical pregnancy rate, miscarriage rate, and live birth rate. Similar fertilization rates per oocyte obtained were observed in IVF and ICSI patients, but significantly lower per mature oocyte in the ICSI group (IVF: 91.5%, ICSI-MF: 75.0%, ICSI-NMF: 77.8%). Although there is no statistical significance, the lower live birth rate is observed in group C than others (A:11.5%, B:25%, C:5%, p = 0.187). Conclusion: In this study, pregnancy outcomes of conventional in vitro fertilization and ICSI in poor responders with only a single oocyte retrieved were similar. However, the fertilization rate of matured oocytes in ICSI groups is significantly lower than that in the IVF group, indicating that ICSI procedures might cause oocyte damage. Therefore, the choice of fertilization method should be based on semen quality. A randomized controlled trial should be performed to confirm our findings.